THE INFLUENCE OF SERVICE QUALITY ON CUTOMER SATISFACTION IN HANDLING UMROH TRAVEL DOCUMENTS ON TARA TOUR DURING THE EID 2018 HOLIDAY PERIOD - Harry Yulianda; Pepy Afrilian; Satrio Adhitomo (Imara: JURNAL RISET EKONOMI ISLAM, 2021)
This study aims to find out how the effect of quality of service on customer satisfaction in handlingtravel documents in Tara tour during the holiday period of Eid Al-Fitr 2018. This study uses descriptive methodswith qualitative approach, namely transforming raw data into a form of data that is easy to understand andinterpret, as well as composing, manipulating and presenting in order to become information. The results of thisstudy show that there are several aspects that affect the quality of service, namely the aspects of physical evidence,aspects of reliability, aspects of responsiveness, aspects of assurance and aspects of empathy. From the results ofthis study, the findings that customer satisfaction in handling documents from the aspect of physical evidence(tangible) by 69%, customer satisfaction in handling documents from the aspect of reliability (reliability) of73%, customer satisfaction in handling documents from the aspect of responsiveness (responsiveness) of 72%,customer satisfaction in handling documents from the aspect of assurance (assurance) of 84% and customersatisfaction in handling documents from the aspect of empathy (empathy) of 84%.